Effects of a large-scale participatory learning and action programme in women's groups on health, nutrition, water, sanitation, and hygiene: A cluster-randomized controlled trial in Bihar, India - Lisa Bogler; Christian Bommer; Cara Ebert; Abhijeet Kumar; S. V. Subramanian; Malavika A. Subramanyam; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Evidence from randomized controlled trials suggests that interventions relying on community involvement through a participatory learning and action (PLA) approach can improve health outcomes in resource-poor settings. However, whether PLA-based interventions remain effective after scale-up is only poorly understood. In a cluster-randomized controlled trial in Bihar, India, we assessed whether the PLA approach improved health, nutrition, water, sanitation, and hygiene (HNWASH) outcomes in adults and children when implemented at large scale by a government-supported agency. The intervention consisted of trained female facilitators conducting a series of 20 structured participatory meetings about key HNWASH topics in state-supported women's groups. In contrast to the strong results of small-scale trials, we do not observe systematic improvements in HNWASH knowledge, attitudes, behaviour or health outcomes but document irregularities in the implementation of the intervention. These findings call for caution when promising public health interventions are transformed into large policy programmes.
Keywords: 330; participatory learning and action; women's groups; health; nutrition; HNWASH; Soziale Stabilität; Soziale Integration; Flüchtlinge; Kinder; Jugendliche; Junge Erwachsene; Syrer